Composition of the Assets of Investments in Brazilian Supplementary Private Pension Plan System (EFPC): an exploratory analysis based in the type of patronage - Ribeiro Filho, José Francisco; Libonati, Jeronymo José; Lopes, Jorge Expedito de Gusmão; Santiago, Hugo Leonardo Ferraz (Review of Business Management, 2008)
This study aims to analyze the segments of investment assets in the Brazilian Supplementary Private Pension Plan System (EFPC), typifying them based on public patronage and private patronage. It was used the exploratory inductive method, since, starting with the available data in the site www.previdencia.gov.br, a table was built with the indexes of each type of investment assets, as a percentile of the total investments assets, being considered the exercises of 2002, 2003, 2004 and 2005. The data were tabulated for subsequent hypothesis test. The no-parametric test of Kruskall-Wallis (H) was used, which verifies if k independent samples come from populations with same averages. It was concluded that when the patronage of the fund is made by public entities there is a bias to apply in the titles that the federal, state and municipal governments are responsible for. Whereas, when the fund is sponsored by private entities there is a bias for investments in financial institutions. It was also verified that the public entities direct their resources to invest in shares and in investment funds. Key-words: Brazilian supplementary private pension plan system. Investment. Types of patronage.